Some Special Families of Holomorphic and SÄƒlÄƒgean Type Bi-univalent Functions Associated with \((m,n)\)-Lucas Polynomials - Swamy, S. R.; Wanas, Abbas Kareem; Sailaja, Y. (Communications in Mathematics and Applications, 2020)
The aim of the present paper is to introduce some special families of holomorphic and SÄƒlÄƒgean type bi-univalent functions associated with \((m,n)\)-Lucas polynomials in the open unit disc \(D\). We investigate the upper bounds on initial coefficients for functions in these newly introduced special families and also discuss the Fekete-Szegö problem. Some interesting consequences of the results established here are indicated.